From early child development to human development : Investing in our children's future - Young, Mary Eming (Washington, D.C. : World Bank, 2002)
This book contains essential resources information that includes descriptions and case studies of successful early child development programs throughout the world.
Includes bibliographical references and index.
osa 22/09/2016
Loans
Keywords: Child development; Child health services; Early childhold education